Three-dimensional finite element analysis of occlusal stress on maxillary first molars with different marginal morphologies restored with occlusal veneers - Qing Chen; Siyang Luo; Yujuan Wang; Zhu Chen; Ying Li; Maohua Meng; Yamei Li; Nan Xiao; Qiang Dong (BMC, 2024)
Abstract Background There are differences in the research results regarding which edge design of occlusal veneers can achieve the best long-term success rate as a relatively new fixed prosthesis restoration method. Further research is needed. The three-dimensional finite element method was used to conduct stress analysis on occlusal veneers of maxillary first permanent molars with different thicknesses and margin preparation designs. The aim of this study was to provide mechanical research evidence and a reference for exploring standardized clinical protocols for the design of occlusal veneer restorations of maxillary first molars. Method A 3Shape (Intraoral Scanner) was used to scan the maxillary first molar teeth in vitro, after which 3D printing was carried out. Three different edge designs were applied to identical teeth: straight-beveled finishing line(SFL), chamfer finishing line(CFL), and standard cuspal inclination(SCI). Preparation was carried out with a thickness of 0.5 mm. Using the surface deformation feature, the occlusal veneer was thickened to 0.5 mm and 1.0 mm, and periodontal ligaments were added. They were then placed into the upper and lower jaws and dental arches. Finite element analysis was performed after applying bite force dispersion to the loading area on the mandible following dynamic contact. Results (1) As the thickness increased, the maximum Von Mises stress in the occlusal veneers SFL and CFL also increased, while the SCI exhibited the opposite trend. (2). The trend of the maximum Von Mises stress in the adhesive layer decrease gradually with increasing thickness of the occlusal veneer. The stresses of the SFL and CFL is concentrated primarily at the edge position below the functional cusp, resulting in relatively low adhesive stress. However, in the SCI group, the maximum stress at the edge of the adhesive layer exceeds the maximum shear strength of commonly used adhesives. Conclusions Under the experimental conditions, the mechanical properties of the maximum Von Mises stress in the SFL, CFL, and SCI occlusal veneers meet clinical needs. Incorporating the minimally invasive concept of tooth preservation, a thickness of 1.0 mm are optimal for glass ceramic occlusal veneers on maxillary first molars.